Ruthenium Complexes Bearing Axially Chiral Bipyridyls: The Mismatched Diastereomer Showed Red Circularly Polarized Phosphorescence. Issue 6 (15th December 2021) - Takaishi, Kazuto; Nakatsuka, Yusuke; Asano, Hitomi; Yamada, Yuya; Ema, Tadashi
Abstract: Ruthenium II complexes bearing three axially chiral bipyridyl ligands were synthesized as a new family of chiral complex dyes, and Δ‐( S )‐ and Λ‐( S )‐diastereomers were obtained. The X‐ray crystal structure analyses, spectroscopy, and DFT calculations suggested that all the bipyridyls maintained chirality in both the ground and excited states, and the Δ‐( S )‐ and Λ‐( S )‐isomers are the matched (more relaxed) and mismatched (more constrained) pairs, respectively. The mismatched Λ‐( S )‐isomer exhibited red circularly polarized phosphorescence (CPP) both in solution and in the solid state. The solution state CPP is the most intense of ruthenium complexes, while the solid state CPP is the first example of them. It is supposed that, for the Λ‐( S )‐isomer, the six cumulative CH/π interactions suppress further distortion in the T1 state. Abstract : Ruthenium II complexes bearing axially chiral bipyridyls were synthesized, and matched (more relaxed) Δ‐( S )‐ and mismatched (more constrained) Λ‐( S )‐diastereomers were obtained. The Δ‐( S )‐isomer was nonluminescent. In contrast, the Λ‐( S )‐isomer exhibited vivid red circularly polarized phosphorescence. For the Λ‐( S )‐isomer, the cumulative CH/π interactions seem to suppress further distortion in the T1 state.